Factors affecting the value of land passed by railroad tracks in the campus area Yogyakarta - Merina, Bresca (Trigin Publisher, 2024)
This research aimed to determine the factors that influence the land value of the railway train around the campus area in Timoho Yogyakarta. In this research, the sample of land value is taken from the land value population located around the railway train at Timoho area that is surrounded by campus, limited by four districts there are Kota Baru district and Demangan in the north and Baciro district and Muja-muju district in the south. The control area uses a land value survey in the Janti district in the north and Gedong Kuning district in the south. The technique of collecting data is from observation in location. The finding of this research shows that the distance of the land to the railway and campus influenced land value and the size of the land influenced land value. Public transportation is not influenced land value. The land access by railway trains influenced land value. The shape of land is not influenced land value.